Effects of Lagenaria siceraria (Molina) Standl polysaccharides on growth performance, immune function, cecum microorganisms and short-chain fatty acids in broilers - Zhang, Zhenping; Dong, Shiqi; Li, Jinrong; Aizezi, Maimaiti; Huang, Peng; Abula, Saifuding; Mai, Zhanhai; Liu, Dandan; Wusiman, Adelijiang (Frontiers in Veterinary Science, 2024)
In this study, Lagenaria siceraria (Molina) Standl polysaccharides (LSP) was prepared using the water-alcohol precipitation method to evaluate its effects on growth performance, slaughter performance, cytokines, immune organ indices, cecal short-chain fatty acids (SCFAs), and microbial community structure in broiler chickens when added to the basal diet. Seventy-five broiler chickens were selected and randomly divided into five groups, with 15 chickens per group. All groups were fed a basal diet for 7 days. From 7 days of age, the control group continued to receive the basal diet, while the positive drug group was fed a diet supplemented with Astragalus polysaccharides (APS, 100 g/kg) in addition to the basal diet. The experimental groups were fed diets containing different concentrations of LSP (50, 100, and 200 g/kg) in addition to the basal diet, and the supplementation continued for 42 days. The findings indicated that the incorporation of LSP into the feed significantly enhanced average daily weight gain (ADWG), average daily feed intake (ADFI), feed to gain ratio (F/G), dressing percentage, percentage of breast muscle, percentage of leg muscle, and percentage of abdominal fat while concurrently reducing drip loss rate and cooking loss rate (p < 0.01) in comparison to the control group. Additionally, it significantly augmented the levels of interleukin-4 (IL-4) and interleukin-12 (IL-12) in cytokines, secreted immunoglobulin A (SIgA) and immunoglobulin G (IgG) in immunoglobulins, as well as immune organ indicators (p < 0.05). Furthermore, LSP also modulated the intestinal microbiome composition by increasing the abundance of Bacteroides species and significantly changing concentrations of specific short-chain fatty acids (SCFAs) such as propionic acid, isobutyric acid, acetic acid, and isovaleric acid (p < 0.01). These results suggest that dietary supplementation with LSP can effectively regulate intestinal microbiome composition while promoting short-chain fatty acid production. The alterations in microbial characteristics ultimately contribute to improved intestinal immunity and immune organ development as well as enhanced production performance and immune function in broilers.